2021
DOI: 10.1055/s-0041-1729972
|View full text |Cite|
|
Sign up to set email alerts
|

Drug-Induced Vanishing Bile Duct Syndrome: From Pathogenesis to Diagnosis and Therapeutics

Abstract: The most concerned issue in the context of drug/herb-induced chronic cholestasis is vanishing bile duct syndrome. The progressive destruction of intrahepatic bile ducts leading to ductopenia is usually not dose dependent, and has a delayed onset that should be suspected when abnormal serum cholestasis enzyme levels persist despite drug withdrawal. Immune-mediated cholangiocyte injury, direct cholangiocyte damage by drugs or their metabolites once in bile, and sustained exposure to toxic bile salts when biliary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 190 publications
(223 reference statements)
0
20
0
Order By: Relevance
“…Treatment for drug-induced VBDS is largely similar to that for other types of drug-induced cholestasis, including immediate withdrawal of the culprit drug and preventing re-exposure, as well as ursodexycholic acid to protect against toxic bile salts 15,[32][33] . Steroids and other immunosuppressants may be used when there is an indication of allergic reaction such as eosinophilia, lymphadenopathy, rash or syndromes like Stevens-Johnson syndrome 33 . Plasmapheresis has been used successfully in a case of loxprofen-induced ductopenia in an adolescent female unresponsive to initial treatment measures 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for drug-induced VBDS is largely similar to that for other types of drug-induced cholestasis, including immediate withdrawal of the culprit drug and preventing re-exposure, as well as ursodexycholic acid to protect against toxic bile salts 15,[32][33] . Steroids and other immunosuppressants may be used when there is an indication of allergic reaction such as eosinophilia, lymphadenopathy, rash or syndromes like Stevens-Johnson syndrome 33 . Plasmapheresis has been used successfully in a case of loxprofen-induced ductopenia in an adolescent female unresponsive to initial treatment measures 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, the recovery time in UDCA treatment group was even longer (Saito et al, 2016). Additionally, UDCA has recently been recommended for druginduced VBDS with cholestasis (Bessone et al, 2021), although a few cases of inefficacy have been reported .…”
Section: Ursodeoxycholic Acidmentioning
confidence: 94%
“…There is increasing evidence that drugs that are excreted by the liver into bile are prime candidates for producing cholestatic liver disease in the susceptible patient ( Björnsson and Olsson, 2005 ). Many drugs target the biliary epithelium and result in “drug-induced cholangiopathy” and the “vanishing bile duct syndrome” (VBDS), characterized by loss of bile duct >50% due to inflammatory response and necrosis of the intralobular bile duct epithelium ( Padda et al, 2011 ; Bessone et al, 2021 ). Most cases of drug induced cholestasis will resolve with withdrawal of the offending medication and not develop chronic liver disease.…”
Section: Pharmacotherapy Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment for drug-induced VBDS is largely similar to that for other types of drug-induced cholestasis, including immediate withdrawal of the culprit drug and preventing re-exposure, as well as ursodexycholic acid to protect against toxic bile salts. 15,37,38 Steroids have been found to be largely ineffective for treating ductopenia but may be used when there are other indications of an allergic reaction. [39][40][41][42][43] The main indication for their use in this case is the patient's history of panhypopituitarism and the suspicion of a concomitant adrenal crisis.…”
Section: What This Study Adds?mentioning
confidence: 99%